FAKTOR – FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BEI - Rani Milansari; Endang Masitoh; Purnama Siddi (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
This study aims to examine and analyze the factors that influence the capital structure of food and beverage companies listed on the Indonesia Stock Exchange. The population in this study amounted to 26 companies and diporeleh samples of 47 companies using purposive sampling techniques. This study uses secondary data types for the period 2015 - 2018. Analysis of the data used is multiple linear regression analysis. The results showed that the company's current ratio and size affected the capital structure, while the return on assets, asset structure and sales growth did not affect the capital structure. Keywords: CR, ROA, Asset Structure, Capital Structure